Targeting synaptic plasticity in schizophrenia: insights from genomic studies. Issue 11 (November 2021) - Mould, Arne W.; Hall, Nicola A.; Milosevic, Ira; Tunbridge, Elizabeth M.
Abstract : Patients with schizophrenia experience cognitive dysfunction and negative symptoms that do not respond to current drug treatments. Historical evidence is consistent with the hypothesis that these deficits are due, at least in part, to altered cortical synaptic plasticity (the ability of synapses to strengthen or weaken their activity), making this an attractive pathway for therapeutic intervention. However, while synaptic transmission and plasticity is well understood in model systems, it has been challenging to identify specific therapeutic targets for schizophrenia. New information is emerging from genomic findings, which converge on synaptic plasticity and provide a new window on the neurobiology of schizophrenia. Translating this information into therapeutic advances will require a multidisciplinary and collaborative approach. Highlights: Recent genomic findings identify many hundreds of genomic loci that are associated with schizophrenia. Consistent with data from the pregenomic era, genomic findings implicate synaptic function and plasticity as a tractable therapeutic target for the cognitive dysfunction and negative symptoms that patients experience. Genomic findings have the potential to provide insights into the nature of synaptic dysfunction in schizophrenia, and to identify novel therapeutic targets, but identifying the most promising candidates remains a challenge. We propose an integrated approach to triaging the long list of potential genomic targets and provide six practical criteria that we use to prioritise putative candidates.